Fenamiphos Use Facts and Phaseout - Frederick M. Fishel (EDIS, 2019)
This document describes general uses of fenamiphos, addresses specific label requirements regarding its use in Florida, and provides a description of the products phaseout. This document is PI-93, one of a series of the Pesticide Information Office, UF/IFAS Extension. Original publication date January 2006.